Unlawful Acts as a Result of Payment of Compensation Through Royalty Rights Perpsective of Law Number 28 Year 2014 Copyright - Solehah Dhara Ad'ha Br Sianipar; Muhammad Yadi Harahap (Journal Equity of Law and Governance, 2024)
This research focuses on the analysis of compensation through the payment of copyright royalties on music works in the perspective of Law No. 28 of 2014 on Copyright. musical works in the perspective of Law No. 28 of 2014 on Copyright. This research aims to understand how the law regulates the payment of royalties as a form of compensation to music creators and provides protection and compensation to music creators through the provide protection and compensation to music creators through royalty payments and also This research also aims to analyze the study of Decision No. 122/PK/Pdt. Decision Number 122/PK/Pdt.Sus-HKI/2015/PN.Niaga.Jkt.Pst in which there is a case of Royalty Payment Dispute. The verdict is a case of Dispute over Royalty Payments on the Copyright License of Inul Vizta Karaoke VS Yayasan Karya Cipta Indonesia (YKCI) which PT. Vizta Pratama Inul Vizta Karaoke Manado was sentenced to pay royalty compensation to Yayasan Karya Cipta Indoensia in the amount of Rp15,840,000.00 (fifteen million eight hundred forty thousand rupiah). Through the juridical research method normative research method, this research explores the interpretation and implementation of the law in the context of of the law in the context of royalty payments for copyrighted musical works. The results The results of this research are expected to provide a better understanding of the the rights and obligations of the parties in the context of musical copyright and provide recommendations for the improvement and enhancement of copyright protection in And also expected to increase knowledge for readers and provide awareness for the Indonesian people to better appreciate the and also expected to add knowledge for readers and provide awareness for the people of Indonesia to better appreciate the creators of songs or music by paying royalties or music copyright. song or music by paying royalties or no longer pirate, imitating, falsifying, or recognizing as his own creations on the copyright of others or licensees of the copyright of others. copyright of others or the license holder of the creation